The Influence of Organizational Culture, Leadership and Motivation through Job Satisfaction on Staff Performance at Hasanuddin University Hospital - Marlina Ulfa; Nurdjanah Hamid; Wahda Rasyid (Magister Management, Hasanuddin University, 2020)
The study aims to analyze the direct influence of organizational culture, leadership, and motivation on job satisfaction and on staff performance as well as job satisfaction on employee performance at the Hospital of Hasanuddin University. The research is a quantitative study using an analytic observational design with a cross-sectional study approach. Sampling is done by using a proportional random sampling technique. The population in this study were all staff of Hasanuddin University Hospital, totaling 541 people. The total sample of 225 people from the total subpopulation of each unit. Data collection is done by filling out a research questionnaire. Data testing was performed using validity, reliability, and hypothesis testing. Data were analyzed using descriptive analysis and path analysis. The results showed that organizational culture, leadership, and motivation had a direct significant effect on job satisfaction. Further, motivation and job satisfaction have a significant effect on performance. Interestingly, organizational culture and leadership have no significant effect on performance.